1984
DOI: 10.1111/j.1399-0004.1984.tb01106.x
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial deletion of the long arm of chromosome 6 [del(6)(q16q22)]: case report and review of the literature

Abstract: Partial monosomy of 6q resulting from an interstitial deletion of bands q16 → q22 was found in a 12‐year‐old boy manifesting mental retardation, seizure disorder, and dysmorphic features. The correlation of phenotypic expression and specific long arm deletions of chromosome No. 6 is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The five previously reported individuals with seizures had cytogenetically defined deletions that overlapped at 6q22.2q22.32 [12,14,22,68,69], while four individuals have been reported with EEG abnormalities without seizures and molecularly defined deletions involving 6q16, though they do not all overlap each other [1,7,16] (Fig. 2a).…”
Section: Seizures In 6q Deletionsmentioning
confidence: 91%
See 1 more Smart Citation
“…The five previously reported individuals with seizures had cytogenetically defined deletions that overlapped at 6q22.2q22.32 [12,14,22,68,69], while four individuals have been reported with EEG abnormalities without seizures and molecularly defined deletions involving 6q16, though they do not all overlap each other [1,7,16] (Fig. 2a).…”
Section: Seizures In 6q Deletionsmentioning
confidence: 91%
“…Subject 3 has a progressive tremor. Other individuals have been reported with interstitial 6q deletions and ataxia or myopathy [2, 16,17,19,22,68,69], most of whom also had either seizures or a PW-like phenotype (Fig. 5).…”
Section: Movement Disorders In 6q Deletionsmentioning
confidence: 97%
“…In this review, we excluded patients reported here with partial trisomies (due to a parental translocation) in addition to the 6q monosomy, and we excluded reports with insufficient data to allow clinical comparison. A total of 16 patients with a terminal 6q deletion could be reviewed (Dallapiccolla et al 1978, Kueppers et al 1977, Goldberg et al 1980, Shen-Schwartz et al 1989, Meng et al 1992, Stevens et al 1988, mlosevic & Kalicanin 1975, Liberfarb et al 1978, Bartoshesky et al 1978, Rwas et al 1986, Krassikoff & Sekhon 1990, Valtat et al 1992, and McLeod et al 1990) and a total of 21 patients with an interstitial 6q deletion (Slater et al 1988, Lonardo et al 1988, McNeal et al 1977, Young et al 1985, Yamamoto et al 1986, Turleau et al 1988, Valtat et al 1992, Horigomo et al 1991, Nakagome et al 1980, Glover et al 1988, Chery et al 1989, Schwartz et al 1984, Cote et al 1981, Ito et al 1989, Bzduch & Lukacova 1989, Park et al 1988, Matkins et al 1987, McLeod et al 1990, Funs et al 1991, Braverman et a1 1993, Villa et a1 1995, Rose et a l 1992and Narahara et al 1991.…”
Section: Discussionmentioning
confidence: 99%
“…Deletions of the long arm of chromosome 6 are rare, and less than 30 patients with interstitial deletions involving the 6q21q22.1 region have been described to date (Schwartz et al, 1984;Young et al, 1985;Pandya et al, 1995;Correa-Cerro et al, 1996;Evers et al, 1996;Hopkin et al, 1997;Tsukahara et al, 1997;Duran-Gonzalez et al, 2007;Zherebtsov et al, 2007;Rosenfeld et al, 2012;Toschi et al, 2012;Hudson et al, 2014;Szafranski et al, 2015;Tassano et al, 2015;Milani et al, 2016;Shukla et al, 2016;Donahue and Rohena, 2017;Machida et al, 2022). Hopkin et al (1997) first classified deletions of the long arm of chromosome 6 into three groups, based on conventional cytogenetics, with different and recurrent phenotypes: group A, or proximal deletions (6q11q16), group B, or medial deletions (6q15q25), and group C, or terminal deletions (6q25qter) (Hopkin et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Deletions of the long arm of chromosome 6 are rare, and less than 30 patients with interstitial deletions involving the 6q21q22.1 region have been described to date ( Schwartz et al, 1984 ; Young et al, 1985 ; Pandya et al, 1995 ; Correa-Cerro et al, 1996 ; Evers et al, 1996 ; Hopkin et al, 1997 ; Tsukahara et al, 1997 ; Duran-Gonzalez et al, 2007 ; Zherebtsov et al, 2007 ; Rosenfeld et al, 2012 ; Toschi et al, 2012 ; Hudson et al, 2014 ; Szafranski et al, 2015 ; Tassano et al, 2015 ; Milani et al, 2016 ; Shukla et al, 2016 ; Donahue and Rohena, 2017 ; Machida et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%